2004
DOI: 10.1002/jnr.20364
|View full text |Cite
|
Sign up to set email alerts
|

Elevated endogenous GABA level correlates with decreased fMRI signals in the rat brain during acute inhibition of GABA transaminase

Abstract: Vigabatrin and gabaculine, both highly specific inhibitors of GABA (gamma-aminobutyric acid) transaminase, cause significant elevation of endogenous GABA levels in brain. The time course of GABA concentration after acute GABA transaminase inhibition was measured quantitatively in the alpha-chloralose-anesthetized rat brain using in vivo selective homonuclear polarization transfer spectroscopy. The blood oxygenation level-dependent (BOLD) effect in functional magnetic resonance imaging (fMRI) has been considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 63 publications
8
56
1
Order By: Relevance
“…This is consistent with a recent study in rat somatosensory cortex (31), which measured the BOLD response after i.v. administration of vigabatrin, a drug that inhibits the action of GABA transaminase (GABA-T), which normally acts to break down GABA.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a recent study in rat somatosensory cortex (31), which measured the BOLD response after i.v. administration of vigabatrin, a drug that inhibits the action of GABA transaminase (GABA-T), which normally acts to break down GABA.…”
Section: Discussionsupporting
confidence: 93%
“…In the question of the effects of GABA-ergic activation, we find no evidence in the literature that increased GABA release per se raises metabolism or blood flow; on the contrary, several recent studies suggest that GABA-ergic inhibition lowers blood flow in the target area [Chen et al, 2005;Roland and Friberg, 1988;Takano et al, 2004;Xi et al, 2002]. Early PET studies suggested that blood flow measures might fail to distinguish between increased GABA-ergic inhibition and increased glutamatergic excitation, as both require energy and both may benefit from increased blood flow [Ackermann et al, 1984].…”
Section: Discussioncontrasting
confidence: 92%
“…Chen and colleagues (Chen et al, 2005) demonstrated that elevated endogenous GABA levels, elicited using vigabatrin in rats, reduced stimulus induced BOLD responses to forepaw stimulation. In humans, several studies have looked at the correlation of GABA with positive BOLD responses.…”
Section: Bold and Mrs Studiesmentioning
confidence: 99%